Lateral opening of main bile duots in hydatic adventitia.: lts treatment by cyst-biliary disconnection - Perdomo, Roberto; Geninazzi, Héctor; Santana, Carlos; López, Julio; Castro, Danilo; Morelli, Raúl; Bertolini, Carlos; Ruocco, Alvaro; Carbó, Alberto (Cirugía del Uruguay, 1984)
In its expansiva evolution the hepatic hydatid cyst produces lateral or terminal piercing in main bile ducts, biliary or juxtabiliary. Said piercing cause immediate post-operativa bilirrhage of variable duration and volume. When the bile running stops, it means that !he opening has healed up and_ therefore, that !he canal where it is located is -often- wholly or partially stenosed.